Manfaat Karunia Roh Untuk Membantu Pertumbuhan Gereja - Kus Suhatmaji (STT Kingdom, 2024)
The aim of the research is to explore the benefits of the gifts of the Holy Spirit to help church growth, where here we discuss the meaning of Spiritual Gifts, the meaning of congregation growth and the benefits of the gifts of the Spirit in church growth. The method used in this research is qualitative method